Adult intramuscular shoulder angiomyolipoma: a rare case / Kadhim Jawad Obaid … [et al.] - Kadhim Jawad Obaid (Faculty of Medicine, 2016)
Intramuscular shoulder angiomyolipomas are very rare. We report a case in a 22-year-old male with a well circumscribed lesion located on the back of the shoulder. This lesion, differs from renal angiomyolipoma in terms of non-association with tuberous sclerosis, circumscription and male predominance. Another characteristic feature is the absence of epithelioid cells. Differential diagnosis includes lipoma, angiolipoma, angioleiomyoma, hemangioma, myolipoma and liposarcoma. It is distinguished from the above mentioned entities by the presence of a combination of thick-walled blood vessels, smooth muscle and fat.